Validation of a short version of the Organizational Communication Climate for Portugal and Italy - Sampayo, M.M.; Carvalho, H.; Silva, S.A. (14th European Conference on Psychological Assessment, 2017)
The main aim of the present research is to contribute to the validation of the Communication Climate Scale (Smidts et al., 2001) for Portuguese and Italian samples by verifying: whether it shows the same two-factor structure (construct validity); whether it significantly correlates with extra-role criterion-related variables (voice, cynicism, safety participation). The psychometric properties of the scale were explored by using two Portuguese samples of professionals from different sectors in two studies (Study I: n= 277, Study II n = 167) and one Italian sample of blue collar workers, belonging to the metal-mechanical sector (Study III n =244). All data were collected at individual level. Exploratory Factorial Analysis (EFA) were performed in the first two studies, Confirmatory Factorial Analysis (CFA) were performed in the three studies (Portugal and Italy) using Structural Equation Modelling. Results showed that Portuguese and Italian version of the scale have good psychometric proprieties. Results of the construct validity of the scales confirmed a two dimensional structure (trust and openness; supportiveness) with 9 items for the Portuguese and Italian version, with robust psychometric proprieties that may be used in future studies concerning the communication climate in organizations. Furthermore, the predictive validity results revealed that the dimension Trust and Openess predicted voice (more voice behaviors) and cynicism (less cynicism) in the Portuguese study and safety participation (more safety participation behaviors) in the Italian study.